Utilization of Semi Natural Media With Hydrolysis Method Using Pepaya and Pineapple for Growth of Pseudomonad Fluorescent Isolate Pf-122 - Y. Wuryandari; S. Wiyatiningsih; Suwandi; H.F. Wati (Future Science)
Pseudomonad fluorescent isolate Pf 122 is a biological agent bacteria that is often used to control soil borne pathogens. The aim of the study was to determine the growth of bacteria in a variety of semi-natural media that have been hydrolyzed by using papaya or pineapple and those that are not hydrolyzed. The media is expected to be used as a substitute for Kings' B, which is relatively expensive, for the growth of Pseudomonad fluorescent. This study was compiled using a Completely Randomized Design (CRD) with 13 treatments and repeated 4 times on a laboratory scale. The research treatment consisted of several media including Kings' B, crab, pineapple crab, papaya crab, snail, pineapple snail, papaya snail, lamtoro, pineapple lamtoro, papaya lamtoro, tolo, pineapple tolo and papaya tolo. The results showed the highest population of bacteria in the medium of crabs and snails. The average population of bacteria in semi-natural media is more than the population of bacteria in the Kings ‘B media. The growth of bacteria is the second best, namely bacterial growth in pineapple crab media, papaya crab, anyway, Kings'B. Media that is not good for bacteria growth are pineapple snail, papaya snail, pineapple toasted, pineapple lamtoro and papaya lamtoro because it doesn’t show the growth of bacteria. Compared to crab, snail and pineapple crab media, growth of Pseudomonad fluorescent isolate Pf 122 bacteria shows significant differences with Kings 'B. Thus the medium of crabs, snails, pineapple crabs and tolo can be used as a substitute for Kings' B.